Predictive Value of Gensini Score in the Long-Term Outcomes of Patients With Coronary Artery Disease Who Underwent PCI - Wang, Kai-Yang; Zheng, Ying-Ying; Wu, Ting-Ting; Ma, Yi-Tong; Xie, Xiang (Frontiers in Cardiovascular Medicine, 2022)
Abstract: Objective: Gensini score is an effective tool used to evaluate the severity of coronary artery disease(CAD). Whether the Gensini score has predictive value for the clinical outcomes of patients with CAD after PCI has not been investigated. Methods: All patients were from the CORFCHD-PCI, a retrospective cohort study involving 5672 CAD patients who underwent PCI, including 2110 patients with diabetes and 3562 patients without diabetes, from January 2008 to December 2016. Patients were divided into 3 groups according to the tertile of Gensini score: 1st tertile(Gensini score <11 points), 2nd tertile(Gensini score 11–38 points), 3rd tertile(Gensini score >38 points). The average follow-up time was 35.9±22.6 months. Compare the differences in clinical outcomes between the groups. Multivariate Cox regression analyses were performed to assess the predictive value of Gensini score for outcomes over up to 10 years of follow-up. Results: In the population without diabetes, there were significant differences between the 3 groups in the incidences of ACM (P=0.048), CM (P=0.024), MACE (P=0.006), and MACCE (P=0.009). In the population with diabetes, there were significant differences between the 3 groups in the incidences of ACM, CM, MACE, and MACCE (all P<0.001). After multivariate Cox regression analyses, in the population without diabetes, the respective risks of ACM, CM, MACEs and MACCEs were increased 89.9% (HR=1.899, 95%CI: 1.285-2.807, P=0.001) , 115.1% (HR=2.151, 95%CI: 1.378-3.356, P=0.001), 48.1% (HR=1.481, 95%CI: 1.152-1.904, P=0.002), and 49.8% (HR=1.498, 95%CI: 1.176-1.907, P=0.001) in the 3rd tertile compared with those in the 1st tertile. In the population with diabetes, the respective risks of ACM, CM, MACEs and MACCEs were increased 248.5%(HR=3.485, 95%CI: 1.973-6.154, P<0.001), 260.4% (HR=3.604, 95%CI: 1.866-6.963, P<0.001), 130.2% (HR=2.302, 95%CI: 1.649-3.215, P<0.001), and 119.8%(HR=2.198, 95%CI:1.600-3.018, P<0.001) in the 3rd tertile compared with those in the 1st tertile. Conclusion: The present study indicated that the Gensini score is an independent predictor of long-term adverse outcomes in patients with CAD who underwent PCI, and it has more predictive value in the population with diabetes.